Relationships between the motorcyclists’ behavioural perception and their actual behaviour - Topolšek, Darja; Dragan, Dejan (Transport, 2018)
The paper deals with studying the relationships between the motorcyclists’ thinking about proper behaviour and their actual behaviour in the traffic. The impact of some control variables, such as riders’ age, experience, driving history, and engine cubature, on actual behaviour, is also addressed here. For the purpose of research, two additional questionnaires were applied besides the well-known Motorcycle Rider Behaviour Questionnaire (MRBQ). To examine the causal relations between all-important latent factors present in this study, the structural equation model was designed. Exploratory and confirmatory factor analyses were also engaged in the analysis and the statistical modelling process. The results show that the higher awareness about alcohol danger and benefits of protective equipment and helmet can noticeably contribute to the bigger traffic safety. Besides, from the results is evident that the control variables are in most cases also significantly interrelated with the actual behaviour factors. The findings of this research could be important for the planning of better traffic safety strategies for the motorcyclists to decrease the fatalities and related costs and traumas.First published online 29 February 2016